Importance of Histological Diagnosis for the Specific Oncologic Treatment for Lung Cancer - Yoana Herrera Leiva (Revista Finlay, 2019)
Lung cancer is one of the most frequent neoplasms worldwide, its incidence increases by 0.5 % annually. In Cuba it represents the first cause in cancer mortality and its estimated incidence is 4 500 patients per year. In the Cienfuegos province Oncology Service during the year 2017 approximately 70 patients with cyto-histological confirmation of lung cancer were received for treatment. Consequently it is necessary to expose some general considerations about the importance of making a correct anatomo-pathological diagnosis, with the purpose of providing patients with different therapeutic options to treat their condition.